SUCCESSFUL USE OF SUBCUTANEOUS CONTINUOUS GLUCOSE MONITORING (CGM) IN A DIABETIC PATIENT WITH ACUTE CORONARY SYNDROME (ACS) UNDERGOING CORONARY ARTERY BYPASS GRAFT (CABG) SURGERY: A CASE REPORT - Balansag, Charmia Kim; Robles, Jeremyjones (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Type 2 diabetes mellitus patients undergoing CABG for multi-vessel coronary artery disease (CAD) have a prevalence of greater than 30%. Previous trials demonstrated that subcutaneous CGM is less reliable in cardiac surgeries related to electrocautery interference, signal loss, and hypoperfusion. We present a case of a 59-year-old Filipino male,hypertensive, with poorly controlled diabetes, admitted for chest pain and was managed as ACS Non—ST-segment Elevation Myocardial Infarction (NSTEMI). The coronary angiogram showed CAD-3 vessel disease (99% occlusion left anterior descending artery). FreeStyle Libre (FSL) subcutaneous sensor was attached prior to CABG. Insulin intravenous infusion was started. CGM measured glucose levels completely without signal loss in the peri-operative phases within the target blood glucose in the ICU (90-180 mg/dl (time in the range [TIR]: within 100%, above 0%, below 0%). The patient was discharged and improved on the eighth postoperative day. CGM subcutaneous devices are capable of intensive glucose monitoring during major cardiac surgery while reducing workload. Investigations with larger patient numbers are needed.